PSYCHOLOGICAL MECHANISMS UNDERLYING AGGRESSIVE BEHAVIOR IN FREE FIRE GAMERS WITHIN THE CONTEXT OF KERINCI MALAY CULTURE - Yandri, Hengki; Juliawati, Dosi; Kholidin, Farid Imam; Rasmita, Rasmita; Daflaini, Daflaini (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
This study investigates the psychological mechanisms underlying aggressive behavior among Free Fire gamers in the context of Kerinci Malay culture. By employing in-depth interviews, this research explores the interplay between cultural values, game-related experiences, and individual psychological factors. A case report of an individual (HA) exhibiting Free Fire addiction and a propensity for aggression was conducted. Thematic analysis was employed to analyze the data. Findings indicate that a confluence of factors, including cultural concepts of honor and esteem, customs and traditions, social context contribute to aggressive tendencies. These results highlight the need for a comprehensive understanding of cultural and psychological determinants of online aggression to develop effective prevention and intervention strategies.